Analisis Transformasi Bahasa Gaul dalam Komentar Tiktok Unggahan @iniganta - Windi Putri Lestari; Risnawaty Risnawaty (Pusat riset dan Inovasi Nasional, 2025)
. This research analyses the transformation of slang among Indonesian youth, particularly on the TikTok platform, as an indicator of shifts in communication and cultural trends. Using a qualitative approach and content analysis, this study focuses on the use of slang in TikTok comments to understand the meaning and context of frequently used terms. We randomly collected data from comments made by TikTok users who actively use slang. The analysis results show that the term